Effect of Eccentricity on Breakout Propagation around Noncircular Boreholes - Mohammad Bahrehdar; Ali Lakirouhani (Advances in Civil Engineering)
Investigating the shear failure caused by the concentration of compressive stress around noncircular boreholes is important both in the field and in the laboratory. This article deals with the numerical analysis of elliptical boreholes under a nonisotropic in situ stress field using the Mogi–Coulomb nonlinear failure criterion. The purpose of the presented numerical model is to simulate the progressive shear failure (breakout) around the borehole and investigate the impact of the eccentricity of the borehole on the stability and depth and width of the failure area. According to the obtained results, the breakout is V-shaped and is formed along the minimum principal stress. As the eccentricity of the borehole increases, the final dimension of the breakout becomes smaller; in other words, the increase in ellipticity strengthens the borehole against shear failure. However, as the eccentricity increases, the stress concentration at the breakout tip increases. Another finding of the study conducted in this article is the significant relationship between the width and the depth of the breakout failure, which makes the idea of estimating both horizontal in situ stresses using breakout dimensions seriously doubtful. Also, the interesting result obtained is that the stress concentration factor at the breakout tip for boreholes with different eccentricities is the same at the end of the breakout.